La planificación estratégica y el desarrollo organizacional en la Cooperativa Sol de los Andes de la ciudad de Riobamba 2023 - Chambi Paguay, Yerling Yigiola (2024)
ABSTRACT: The main purpose of this research study was to analyze the relationship between strategic planning and organizational development in the Sol de los Andes Cooperative. We sought to determine whether the implementation of an adequate strategic planning significantly influences the strengthening and improvement of the cooperative's organizational development. In order to carry out this research, a hypothetical deductive approach was adopted, this implies that hypotheses on the influence of strategic planning on organizational development were raised, which were subjected to empirical verification through data collection and analysis. The methodology used was of an explanatory, descriptive and field nature, which allowed characterizing and detailing the current situation of strategic planning and organizational development in the Sol de los Andes Cooperative. For data collection, a survey questionnaire was applied to the cooperative's workers, who are key actors in the organizational processes. Subsequently, the data obtained were processed and analyzed using SPSS statistical software. This tool provided the ability to perform quantitative analyses and obtain numerical and statistical results on the variables studied. One of the key findings to test the study hypothesis was the Chisquare result, which yielded a value of 12.611. This led to rejecting the null hypothesis and accepting the alternative hypothesis, which suggests that strategic planning does have an impact on organizational development. Throughout these results, the study outlines an integral diagnosis, a solid theoretical analysis and finally, the formulation of specific planning strategies regarding the optimum organizational development of Sol de los Andes Cooperative. These strategies would be aimed at strengthening key aspects such as organizational structure, inter-processes, human talent management, organizational culture and the adoption of changes, all aligned with the vision, mission and strategic objectives of the cooperative.